Diagnosis of pulmonary embolism with CT pulmonary angiography: a systematic review. Issue 3 (23rd February 2006) - Hogg, K; Brown, G; Dunning, J; Wright, J; Carley, S; Foex, B; Mackway-Jones, K
Abstract : Objective: To appraise the evidence on the diagnostic accuracy of CT pulmonary angiography and the prognostic value of a negative CT pulmonary angiogram in the diagnosis of pulmonary embolism. Methods: Medline, EMBASE, and grey literature were systematically searched by two researchers. Any study which compared CT pulmonary angiography to an acceptable reference standard or prospectively followed up a cohort of patients with a normal CT pulmonary angiogram was included. Study methods were appraised independently by two researchers, and data were extracted independently by three researchers. Results: Thirteen diagnostic and 11 follow up studies were identified. Studies varied in prevalence of pulmonary embolism (19–79%), patient groups, and method quality. Few studies recruited unselected emergency department patients. There was heterogeneity in the analysis of sensitivity (53 to 100%), specificity (79 to 100%), and false negative rate (1.0 to 10.7%). The pooled false negative rate of combined negative CT pulmonary angiography and negative deep vein thrombosis testing was 1.5% (95% CI 1.0 to 1.9%). Conclusion: Diagnostic studies give conflicting results for the diagnostic accuracy of CT pulmonary angiography. Follow up studies show that CT pulmonary angiography can be used in combination with investigation for deep vein thrombosis to exclude pulmonary embolism.